2015
DOI: 10.1590/1983-21252015v28n421rc
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Quality of Soybean Seeds Under Mechanical Injuries Caused by Combines

Abstract: -The mechanical harvesting causes injuries on seeds and may affect their quality. Different threshing mechanisms and their adjustments may also affect the intensity of impacts that machines cause on seeds. So, this study aimed at diagnosing and evaluating the effect of two combines: the first one with a threshing system of axial flow and the other one with a threshing system of tangential flow, under adjustments of concave opening (10 mm, 30 mm and 10 mm for a combine with axial flow and 3.0 mm, 15 mm and 3.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Among the data from non-injured seeds 1-and 2-years old supported that idea. In one of the studies (Pacheco et al, 2015) [9] , soybean seeds were harvested at two moisture content (16,6% and 13,7%) and combine adjusted three different threshing (highest, lowest, and ideal). Their results showed that the lesser moisture content and the highest threshing caused significantly broken seeds, lesser seed viability, seed vigor, and germination capacity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the data from non-injured seeds 1-and 2-years old supported that idea. In one of the studies (Pacheco et al, 2015) [9] , soybean seeds were harvested at two moisture content (16,6% and 13,7%) and combine adjusted three different threshing (highest, lowest, and ideal). Their results showed that the lesser moisture content and the highest threshing caused significantly broken seeds, lesser seed viability, seed vigor, and germination capacity.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, not only visible damage, but also invisible damage can affect seed physiology, quality, seedling, and full-grown plant growth. Most of the studies on this subject have been on seed damage caused using mechanical tools or combines during harvest (Pacheco et al, 2015;Govindaraj et al, 2017;Gu et al, 2019) [9,6,7] . There are some studies and reviews that indicate the effects of mechanical injury on increasing infection (Bell, 1974;Lamichhane et al, 2020;Rehman et al, 2021) [3,8,10] .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Souza, Albuquerque, Zorato and Carvalho (2009), analysing mechanical damages and quality of cotton seeds, found that the cuts and deep fissures, including those that reach the embryo, lead to reductions in seed germination and vigour. Still, Pacheco et al (2015), studying physiological quality of soybean seeds under mechanical injuries caused by combines, have realized that the mechanical injury has most affected seed quality reductions.…”
Section: Asmentioning
confidence: 99%
“…With the interaction effect between plants and harvesting rollers, the soybeans are harvested. After material delivery, blade cleaning, impurity removal, and pod collection, the mechanized harvesting of green soybean plants is realized [ 14 ]. The harvester using a vertical roller has the advantages of simple structure, one-stage sorting, detachment rate of 92%, and damage rate of 20.8%, however, it can only adapt to high ridge planting rather than flat planting and the damage rate is also too high.…”
Section: Introductionmentioning
confidence: 99%